Apocalyptic Narrative in Hujan Novel By Tere Liye: An Ecocritical Study - Triatuti Triastuti; Anshari Anshari; Suarni Syam Saguni (HUMAN: South Asian Journal of Social Studies, 2021)
This research is a study of the text in the novel using an ecocritical approach with apocalyptic narrative case studies. The data in the study were processed by data reduction, data presentation, drawing conclusions and verification. The object of this research is texts that contain apocalyptic narrative content. The apocalyptic characteristics consist of three elements, including: apocalyptic narrative, elements of heroes and elements of vision. Therefore this research is focused on three problem formulations, namely (1) How is the apocalyptic narrative contained in Tere Liye's Rain novel? (2) How is the hero element to apocalyptic narrative in Tere Liye's Rain novel (3) How is the vision of saving the environment in the novel? Rain by Tere Liye. The results of the analysis show that First, the apocalyptic element in the novel is a threat of universal extinction because the earth is uninhabitable due to extreme hot weather. This is triggered by human ethics who utilize technology with a mechanistic-reductionistic nature. Second, the hero elements in the novel are imaged by the characters of Esok and other members of the consortium who are guided by professors. Third, the element of vision found is the vision of saving humanity from extinction by creating a new habitat in the form of spacecraft as a substitute for the earth. From the results of the study of Tere Liye's novel Hujan, it was found that the three apocalyptic elements were contained coherently.